Rapid Detection of Neisseria gonorrhoeae Genomic DNA Using Gold Nanoprobes Which Target the Gonococcal DNA Uptake Sequence - Carter, Ella; Davis, Sean A.; Hill, Darryl J. (Frontiers in Cellular and Infection Microbiology, 2022)
The rapid spread of antimicrobial resistant Neisseria gonorrhoeae continues to pose a serious threat to global health. To successfully treat and control gonococcal infections, rapid diagnosis is critical. Currently, nucleic acid amplification tests are the recommended diagnostic, however, these are both technically demanding and time consuming, making them unsuitable for resource-poor clinics. Consequently, there is a substantial need for an affordable, point-of-care diagnostic to use in these settings. In this study, DNA-functionalised gold nanoparticles (gold nanoprobes), with the ability to specifically detect the DNA Uptake Sequence (DUS) of Neisseria gonorrhoeae, were prepared. Using complimentary annealing, the gold nanoprobes were shown to hybridise to genomic gonococcal DNA, causing a significant shift in their salt stability. By exploiting the shift in nanoprobe stability in the presence of target DNA, a solution-based colorimetric diagnostic for gonococcal DNA was prepared. Detection was achieved in under 30 minutes, with a clinically relevant detection limit of 15.0 ng of genomic DNA. Significantly, testing with DNA from other gram-negative bacteria indicated good specificity to Neisseria gonorrhoeae. These results show that DUS-specific gold nanoprobes are a promising tool for rapid point-of-care diagnosis of gonococcal infections.